A Randomized Control Comparative Trial of Nebulized Magnesium Sulfate and Hypertonic Saline In Acute Bronchiolitis - G. Chandra Sekhar; Ramisetty M Umamahesh (Asian Journal of Clinical Pediatrics and Neonatology, 2021)
Introduction: Acute bronchiolitis is the common lower respiratory tract illness requiring hospitalization in children < 2years. Vaious treatment modalities proposed to manage the acute bronchiolitis. But no study has been recommended for the treatment other than supportive management. Hence this study aims to study the efficacy of nebulized magnesium sulfate in acute bronchiolitis. Subjects and Methods: A hospital-based randomized prospective comparative clinical observational study conducted in 110 children with mild to moderate bronchiolitis, randomly divided into two groups; Group 1 received 4 ml of hypertonic saline nebulization with 100% oxygen at an interval of 20mins for the first    three doses and then 4th hourly. Group 2, received 0.1-0.2 ml/kg/dose of 25% magnesium sulfate made to 4ml with 0.9% normal saline. Heart rate, oxygen saturation, respiratory rate, and Respiratory Distress Assessment Instrument (RDAI) scores were monitored throughout the study. Results: The mean age was 7.5 + 3.2 months, 6.5 + 3 months in group 1, and group 2 without significant difference(p=0.6). 30(54.54%) cases, and 25(45.45) cases belongs to mild and moderate category of bronchiolitis in group1, and 28(52.7%) cases and 27 (47.27%) cases belongs to the mild and moderate category of bronchiolitis in group 2 (p>0.05). 8(14.54%) cases had leukocytosis and 2 (3.63%) cases had leucopenia in group 1, whereas, Leukocytosis and leucopenia were present in 12(21.81%) and 2(3.63%) cases respectively in group 2. The most common chest X-ray findings in acute bronchiolitis were hyperinflation followed by segmental atelectasis. The mean hospital stay in nebulized with hypertonic saline and magnesium sulfate was 3.5 + 1.0 days and 3.0 + 1.1 days, respectively. The length of hospital stay between hypertonic saline and magnesium sulfate group was slightly longer in moderate bronchiolitis. Conclusion: The mean hospital stay in nebulized with hypertonic saline is higher than and magnesium sulfate. RDAI score does not vary significantly between two groups after nebulization. Further trials with large sample size, the inclusion of children with severe bronchiolitis, and assessment of long-term outcomes are recommended.